2009
DOI: 10.1634/theoncologist.2009-0104
|View full text |Cite
|
Sign up to set email alerts
|

Trabectedin

Abstract: After completing this course, the reader will be able to:1. Enumerate the clinical indications for trabectedin therapy.2. Describe the mechanism of action and the pharmacokinetics of trabectedin.3. Analyze the toxicity profile and appraise the therapeutic effects associated with trabectedin.This article is available for continuing medical education credit at CME.TheOncologist.com. CME CME INTRODUCTIONTrabectedin (ET-743, Yondelis; Ortho Biotech Products, Horsham, PA) is a natural product that was originally is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition, the exclusion of patients with known active liver disease and close monitoring during treatment provided adequate opportunity to deny, adjust, delay or discontinue treatment using established guidelines [24,38]. Notably, the incidence of bilirubin and alkaline phosphatase elevations was very low and neither was cumulative.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the exclusion of patients with known active liver disease and close monitoring during treatment provided adequate opportunity to deny, adjust, delay or discontinue treatment using established guidelines [24,38]. Notably, the incidence of bilirubin and alkaline phosphatase elevations was very low and neither was cumulative.…”
Section: Discussionmentioning
confidence: 99%
“…ET-743 is a natural product isolated from the sea squirt Ecteinascidia turbinate. The drug has been extensively studied in phase I and II studies in sarcomas in both the United States and Europe and found to have activity in leiomyosarcoma, liposarcoma, malignant fibrous histiocytoma, and synovial sarcoma (Chuk et al, 2009;Thornton, 2010). However, the most impressive response rates have occurred in myxoid liposarcoma where an almost 50% response rate has been observed in some series (Grosso et al, 2009;Cesne et al, 2012).…”
Section: Et-743 (Ecteinascidin 743 Trabectedin Yondelis™)mentioning
confidence: 99%
“…Moreover, particularly in oncology, high-potency agents have been developed, which are administered in only a few milligrams. Examples are the marinederived product trabectedin (recommended dose of 1.5 mg/m 2 ) [6] and the marine sponge product analogue eribulin (recommended dose of 1.4 mg/m 2 ) [104]. The extended collection times as well as the low doses pose challenges to the sensitivity of the quantitative assays [7,8].…”
Section: Bioanalytical Assay Development and Validationmentioning
confidence: 99%